نشاط التيار الاصلاحي في الجزائر من خلال كتابات عبدالكريم بوصفصاف 1931-1962م - محمد لمين بن مسعود; د/ عبدالرحمان قفاف (جامعة عمار ثليجي بالاغواط, 2025)
الملخص: تهدف هذه الدراسة إلى البحث في موضوع نشاط التيار الإصلاحي في الجزائر من خلال كتابات عبد الكريم بوصفصاف 1931م- 1962م، الذي يعد من أبرز المؤرخين الذين كتبوا في تاريخ الجزائر في الفترة المعاصرة، قسمت هذه الدراسة إلى ثلاث فصول، تناولت في الفصل الأول التيار الإصلاحي في الجزائر 1931م-1962م، والذي تناولت فيه مفهوم الحركة الإصلاحية في الجزائر وجذورها، عوامل ظهور الحركة الاصلاحية في الجزائر، أهداف ووسائل الحركة الإصلاحية في الجزائر، أما في الفصل الثاني بعنوان السيرة الذاتية لعبد الكريم بوصفصاف، تناولت فيه التعريف بعبد الكريم بوصفصاف، رحلاته العلمية، عبد الكريم بوصفصاف والبحث العلمي، أما الفصل الثالث بعنوان نشاط التيار الاصلاحي من خلال مؤلفات عبد الكريم بوصفصاف 1931م-1962م، والذي تطرقت فيه الى منهجه في الكتابة التاريخية، كتاباته حول الحركة الاصلاحية في الجزائر(1931م-1954م)، التيار الإصلاحي والثورة الجزائرية (1954م-1962م)، وفي الأخير في الخاتمة توصلت الى اهم النتائج والاستنتاجات. الكلمات المفتاحية: التيار الإصلاحي، عبد الكريم بوصفصاف، الكتابة التاريخية، الثورة الجزائرية. ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــ Abstract: This study aims to research the subject of the activity of the reformist movement in Algeria through the writings of Abdel Karim Boussaf 1931 AD - 1962 AD, who is considered one of the most prominent historians who wrote on the history of Algeria in the contemporary period.This study was divided into three chapters, in the first chapter it dealt with the reformist movement in Algeria.1931 AD - 1962 AD, in which it dealt with the concept of the reform movement in Algeria and its roots, the factors for the emergence of the reform movement in Algeria The goals and means of the reform movement in Algeria.As for the second chapter, entitled The Biography of Abdel Karim Boussaf, it deals with introducing Abdel Karim Boussaf, his scientific travels, Abdel Karim Boussaf and scientific research.As for the third chapter, entitled The activity of the reformist movement through the works of Abdel Karim Boussaf 1931-1962 AD, In which I touched on his approach to historical writing, his writings about the reform movement in Algeria (1931 AD - 1954 AD) The reformist movement and the Algerian revolution (1954 AD - 1962 AD), and finally in the conclusion, I reached the most important results and conclusions. Keywords: reformist current, Abdelkarim Boussaf, historical writing, Algerian revolution.